Good Corporate Governance in Islamic Banking during Fourth Industrial Revolution Era - Delina Herdian Septiani; Linda Nurlaela; Arim Nasim; Elis Mediawati (Islamic Research, 2022)
The purpose of this study is to analyze information about implementation of Corporate Governance in Islamic banking. This study uses a quantitative approach with a systematic literature review method from various journals. With the systematic literature review method, the authors identify all empirical evidence, where the identification aims to answer questions such as "How is the implementation of Good Corporate Governance (GCG) in Indonesian Islamic banking?", "What is the role of the Shariah Supervisory Board?", "What is the impact of implementing GCG?". The results of the analysis found that the implementation of GCG in Islamic banking was quite good but still not effective. This is because the governance mechanism is still not fully in accordance with Shariah principles. Therefore, the role of DPS in the implementation of GCG is very important and must be optimized. This finding also opens information about the development of GCG in Islamic banking today so that it can be used as reference material for further research.